Economic Evaluation of Endovascular Treatment for Acute Ischemic Stroke. Issue 3 (14th October 2021) - van den Berg, Lucie A.; Berkhemer, Olvert A.; Fransen, Puck S.S.; Beumer, Debbie; Lingsma, Hester; Majoie, Charles B.M.; Dippel, Diederik W.J.; van der Lugt, Aad; van Oostenbrugge, Robert J.; van Zwam, Wim H.; Roos, Yvo B.; Dijkgraaf, Marcel G.W.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: Endovascular treatment for acute ischemic stroke has been proven clinically effective, but evidence of the cost-effectiveness based on real-world data is scarce. The aim of this study was to assess whether endovascular therapy plus usual care is cost-effective in comparison to usual care alone in acute ischemic stroke patients. Methods: An economic evaluation was performed from a societal perspective with a 2-year time horizon. Empirical data on health outcomes and the use of resources following endovascular treatment were gathered parallel to the MR CLEAN trial (Multicenter Randomized Clinical Trial of Endovascular Treatment for Acute Ischemic Stroke in the Netherlands) and its 2-year follow-up study. Incremental cost-effectiveness ratios were calculated as the extra costs per additional patient with functional independence (modified Rankin Scale score 0–2) and the extra cost per quality-adjusted life year gained. Results: The mean costs per patient in the intervention group were $126 494 versus $143 331 in the control group (mean difference, −$16 839 [95% CI, −$38 113 to $5456]). Compared with patients in the control group, more patients in the intervention group achieved functional independence, 37.2% versus 23.9% (absolute difference, 13.3% [95% CI, 4.0%–22.0%]) and they generated more quality-adjusted life years, 0.99 versus 0.83 (mean difference of 0.16 [95% CI, 0.04–0.29]). Endovascular treatment dominated standard treatment with $18 233 saved per extra patient with a good outcome and $105 869 saved per additional quality-adjusted life year. Conclusions: Endovascular treatment added to usual care is clinically effective, and cost saving in comparison to usual care alone in patients with acute ischemic stroke. Registration: URL: https://www.trialregister.nl/trial/695 ; Unique identifier: NL695. URL: https://www.isrctn.com ; Unique identifier: ISRCTN10888758.